Tuturan Imperatif Bermakna Positif pada Spanduk di Kota Pekanbaru - Mhd. Virzha Nafandri Utama; Charlina; Elvrin Septyanti (GERAM: Gerakan Aktif Menulis, 2021)
This study aims to identify the form of imperative speech that positively affects banners in Pekanbaru City and analyses the meaning and function of imperative speech, which positively affects banners in Pekanbaru City. This research includes the form, meaning, and function of imperative speech, which positively affects banners in Pekanbaru City. This type of research is qualitative research with descriptive methods. Data collecting techniques are documentation techniques, by capturing images taken directly, so the real results are obtained. Imperative speech forms with a positive meaning on banners in Pekanbaru City are 33 ordinary imperative, 31 requests, and six prohibitions. Imperative speech with a positive meaning on banners in Pekanbaru City were: 14 orders, 13 requests, ten persuasion, and 33 invitations. Imperative speech functions with a positive meaning on banners in Pekanbaru City are 56 about invitations and 14 about requests.